Electrochemical Sensing Platforms for HER2‐ECD Breast Cancer Biomarker Detection. Issue 1 (27th November 2018) - Freitas, Maria; Nouws, Henri P. A.; Delerue‐Matos, Cristina
Abstract: Screening and early diagnosis are crucial to increase the success of cancer patients' treatments and improve the survival rate. To contribute to this success, distinct electrochemical immunosensing platforms were developed for the analysis of the ExtraCellular Domain of the Human Epidermal growth factor Receptor 2 (HER2‐ECD) through sandwich assays on nanomaterial‐modified screen‐printed carbon electrodes (SPCEs). The most promising platforms showed to be SPCEs modified with (i) gold nanoparticles (AuNPs) and (ii) multiwalled carbon nanotubes combined with AuNPs. The antibody‐antigen interaction was detected using a secondary antibody labelled with alkaline phosphatase and 3‐indoxyl phosphate and silver ions as the enzymatic substrate. The electrochemical signal of the enzymatically generated metallic silver was recorded by linear sweep voltammetry. Under the optimized conditions, linear calibration plots were obtained between 7.5 and 50 ng/mL and the total assay time was 2 h 20 min, achieving LODs of 0.16 ng/mL (SPCE‐MWCNT/AuNP) and 8.5 ng/mL (SPCE‐AuNP), which are well below the established cut‐off value of 15 ng/mL for this cancer biomarker. Abstract :